The impact of post-conflict in the colombian agriculture, an analysis from public management (2014)
Knowing how it has affected the armed conflict in the Colombian population and which measures the government took to fulfill the points agreed at the negotiating table with the armed group outside the law, for this case the FARC, which is the main issue in this essay. The points in the negotiation are 5: Policy on Comprehensive Agricultural Development, Political Participation, End of Conflict, Illicit Drugs and Victims, which will be emphasized in the policies of comprehensive agricultural development as one of the main economic sources of the country, which has suffered in recent decades by armed conflict, generating an increase in poverty and therefore a growth in unemployment, displacement, inequality and violence.